Evaluasi Kebijakan Pelimpahan Kewenangan Bupati dalam Evaluasi APB Desa oleh Camat Agar Sesuai Tujuan Pelimpahan di Kabupaten Nunukan Provinsi Kalimantan Utara - Hasrul; Dandan Haryono; Agus Priyanto (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This study aimed to describe and analyze the evaluation of the policy of decentralizing authority from the Regent to the Sub-District Head in Nunukan District regarding the evaluation of Village Budgetary Allocation (APB Desa) based on the Regulation of the Nunukan Regent No. 31 of 2018 concerning Amendments to Nunukan Regent Regulation No. 54 of 2012 regarding the Decentralization of Some Authorities of the Nunukan Regent to Sub-District Heads in Nunukan District. The research employed a qualitative approach with a descriptive method. Data collection procedures included in-depth interviews, observations, document studies, and triangulation. The main informants were policy formulators and implementers, relevant government agencies (SKPD), and village governments as service recipients. The policy evaluation theory utilized six criteria: effectiveness, efficiency, sufficiency, equality, responsiveness, and accuracy. The analysis revealed that the criteria for evaluating the policy of decentralizing authority from the regent to the sub-district head regarding APB Desa evaluation had not been fully implemented optimally, especially in terms of effectiveness and responsiveness. Several issues identified in the implementation of APB Desa evaluation by sub-district heads in Nunukan District included the absence of SOPs for APB Desa evaluation services, the quality and quantity of human resources in the bureaucracy, and limited sub-district budgets. The researchers recommended policymakers to issue regulations in the form of regional head regulations governing the technical guidelines for APB Desa evaluation by sub-district heads and the necessity of drafting SOPs for APB Desa evaluation services by relevant agencies to ensure that sub-districts have the same standards in providing APB Desa evaluation services.